Boosting durian productivity : (Rural Industries Research Development Corporation, 1996)
This project attemps to find solutions to surmount some of the above constraints. The primary objective is to boost durian productivity in northern Australia. This book introduction of durian varieties and durio species, characteristics of durian cultivars,...